Social representations of reading: central and peripheral elements of these representations among teachers (Práxis Educativa, 2011)
This paper aims to characterize the structure of the social representations of reading held by first and middle-school teachers from city public schools in a city in the interior of Paraná, Brazil. A free word association test was used for data collection. Of the 322 different words recorded, which were processed by the EVOC software, the elements "know", "inform" and "essential" seem to be central. For this group of teachers, reading is essential and necessary for knowledge acquisition. Implications of these meanings of reading and suggestions are presented throughout the paper. Keywords: Reading. Social Representations. Teachers.